Desactivación del oxígeno singulete por el extracto de las cáscaras del fruto de Syzygium Cumini (2019)
Recent research has shown the importance of plant extracts as powerful antioxidants owing to the presence of chemically active components such as polyphenols, anthocyanins, flavonoids, among others. This synergy of the components becomes a possible alternative to the use of antioxidants of synthetic origin. In this study, Syzygium cumini fruit peel was used to determine the antioxidant activity against singlet oxygen. The extract showed appreciable amounts of phenolic groups (about 8.55 AGE mg/g fruit weight). HPLC-DAD characterization showed at least 3 anthocyanins of higher relative abundance (malvidin 3,5-diglucoside, delphinidin 3,5-diglucoside and petunidin 3,5-diglucoside). The percentage of quenching of singlet oxygen was determined at different concentrations of the ethanolic extract, finding a value of 60% at a concentration of 0.39 mg/mL.